2018
DOI: 10.1080/01658107.2018.1483406
|View full text |Cite
|
Sign up to set email alerts
|

Do Optic Canal Dimensions Measured on CT Influence the Degree of Papilloedema and Visual Dysfunction in Idiopathic Intracranial Hypertension?

Abstract: A recent study found that increased optic canal area on magnetic resonance imaging was associated with worse papilloedema in idiopathic intracranial hypertension (IIH). We repeated this study using more accurate computerized tomography derived measurements. Optic canal dimensions were measured from 42 IIH patients and 24 controls. These were compared with papilloedema grade. There was no correlation between any of the optic canal measurements and papilloedema grade and no significant difference in optic canal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The majority of included studies on LCSF op (81%) performed pressure measurement in a lateral recumbent position [ 7 , 9 , 22 , 27 , 28 , 30 35 , 41 , 43 , 63 73 ], and a reference interval in this position from 7.2 to 16.8 mmHg was established. There was no significant difference between the reference intervals in healthy individuals versus pseudo-healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of included studies on LCSF op (81%) performed pressure measurement in a lateral recumbent position [ 7 , 9 , 22 , 27 , 28 , 30 35 , 41 , 43 , 63 73 ], and a reference interval in this position from 7.2 to 16.8 mmHg was established. There was no significant difference between the reference intervals in healthy individuals versus pseudo-healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the anatomical changes in the optic canal to predict visual outcome, but these have shown conflicting results. An MRI study [ 97 ] reported poor visual function and severe papilloedema or optic atrophy in association with a larger optic canal, while a CT imaging study [ 98 ] found no correlation between any of the optic canal measurements and papilloedema grade and no significant difference in optic canal measurements between IIH patients and controls.…”
Section: Patient Monitoring and Prognosismentioning
confidence: 99%
“…[ 26 ] However, studies using CT to delineate bony optic canal anatomy did not find a correlation between optic canal measurements and papilledema grade. [ 27 28 ] In addition, there was no difference in the optic canal measurements between the eyes of patients with asymmetric papilledema, and no significant difference in the canal measurements between IIH patients and controls.…”
Section: Atypical Presentationsmentioning
confidence: 91%
“…Several hypotheses have been proposed for unilateral or asymmetric papilledema, including compartmentation of the perioptic subarachnoid space, optic canal asymmetry, and asymmetry of intraocular pressure (IOP). [ 21 25 26 27 28 29 ]…”
Section: Atypical Presentationsmentioning
confidence: 99%